Studi Literatur: Perbandingan Efektivitas Senyawa Bahan Alam Terhadap ACE Inhibitor Pada Penyakit Hipertensi - Ajeng Ulfa Mustika; Alifah .; Aliffa Nabila; Aulia Fathanisa; Azzahra Nur Khoiriyah; Muhammad Iqbal Rhamadianto (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The purpose of this study is to determine the Comparison of the Effectiveness of Natural Ingredient Compounds against ACE Inhibitors in Hypertension. Hypertension is a chronic disease with an increasing prevalence due to changes in modern lifestyle. The use of ACE inhibitors (ACEIs) such as captopril and benazepril is a pharmacological therapy that is commonly used to control blood pressure. This study aims to compare the effectiveness of synthetic ACEI compounds with natural ingredient compounds based on the mechanism of action and pharmacokinetic aspects. The method used was in the form of a literature review from various online scientific sources by selecting as many as three main journals as references, each discussing pharmacokinetics, bioequivalence, and clinical applications of ACE Inhibitors., with source search conducted through Google Scholar. The results of the study showed that natural compounds as antihypertensive agents, including flavonoids, chlorogenic acid, catechins, phenolic compounds, saponins, α-linolenic acid (ALA), terpenoids, essential oils, Triacetonamine, and hydrophobic (HAA) and aromatic (AAA) amino acids. These compounds work through various mechanisms, such as inhibiting the activity of the ACE enzyme, increasing the production of nitric oxide (NO) for vasodilation, regulating the expression of genes such as PPARγ (Peroxisome Proliferator-Activated Receptor Gamma), decreasing the secretion of the hormones aldosterone and ADH, stabilizing the sympathetic nervous system, and providing anti-inflammatory and antioxidant effects. These various lines of action, both affecting the RAAS and non-RAS systems, have great potential as complementary therapies or effective and safe alternatives for the management of long-term hypertension.